Abundance of microplastics in coastal area surface water at Tok Bali, Kelantan (Journal of Tropical Resources and Sustainable Science (JTRSS), 2025)
Plastic is a man-made material made up of polymers, which are long molecules structured around carbon chains. Microplastic pollution affects the environment by altering habitats and natural processes. Human activities produce plastic waste, which causes pollution to the environment. Tourism areas are one of the highly exposed areas for microplastic pollutants since a lot of activity is held. Tok Bali Beach is a tourist attraction and a resort area for residents around Tok Bali Beach. Therefore, this study is needed to assess the abundance, distribution, and characteristics of microplastics in the surface waters of Tok Bali beach, Pasir Puteh, Kelantan. In this study, 10 sampling points were selected in the beach area to determine the presence of microplastics in the surface water. Photomicroscopic examination, Fourier Transform Infrared Spectroscopy (FTIR) and Scanning Electron Microscopy (SEM) were used to identify the presence of microplastics in surface seawater samples. Five types of microplastics in the surface seawater such as pellets, fibers, fragments, filaments, and films were identified in this study. Photographic microscopy revealed that flakes were the most dominant form, followed by pellets and fibers. These findings highlight the significant presence of microplastics in the surface waters of Tok Bali Beach, emphasizing the need for pollution mitigation and sustainable coastal management.
Keywords: Microplastic; coastal area; surface water; FTIR; SEM